Treatment outcomes for HIV and MDR-TB co-infected adults and children: systematic review and meta-analysis - Isaakidis, P; Casas, E C; Das, M; Tseretopoulou, X; Ntzani, E E; Ford, N (The international journal of tuberculosis and lung disease, 2015)
The incidence of multidrug-resistant tuberculosis (MDR-TB) is increasing in high human immunodeficiency virus (HIV) prevalence settings, with high associated mortality. Treatment outcomes in HIV-co-infected adults and children are poorly documented. To systematically assess treatment outcomes among HIV-MDR-TB co-infected patients. We searched two databases and the proceedings of an annual international conference up to November 2014 for studies reporting on major clinical outcomes among HIV-MDR-TB-co-infected adults and children, and pooled the results using random-effects meta-analysis. Of 4812 abstracts and articles screened, 30 studies providing data on 2578 adults and 147 children were included. Overall pooled treatment success was 56.9% (95% confidence interval [CI] 46.2-67.6), 49.9% (95%CI 38.5-61.2) among adults and 83.4% (95%CI 74.7-92) among children. Mortality was 38% in adults (95%CI 28-48.1) and 11.4% (95%CI 5.8-17.1) in children. Loss to follow-up was higher among adults (16.1%, 95%CI 9-23.2) than among children (3.9%, 95%CI 0.9-6.9). Adverse events were experienced by the majority of patients; however, this was inconsistently documented. The use of fluoroquinolones, aminoglycosides and Group IV drugs appeared to be associated with treatment success. The proportion of HIV-MDR-TB-co-infected patients achieving treatment success was similar to success rates reported among MDR-TB patients in general, regardless of HIV status; however, mortality was higher, particularly among adults, highlighting the need for early diagnosis and more effective treatment regimens.